How Islamic Education's Perspective on Malaqbiq Culture in Mandar Society - Hamzah S. Fathani; Aan Setiawan (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Malaqbiq is a value that describes all attitudes, behaviours, activities, and policies that prioritize kindness, glory, honour, honesty, and positive behaviours based on Mandar cultural values. Qualitative research aims to uncover the perspective of Islamic education on Malaqbiq culture in Mandar society. This research involved community leaders, traditional stakeholders, and religious (Islamic) leaders in Mandar, West Sulawesi. Documentation studies use manuscripts or records from indigenous peoples or institutions and relevant library sources. The collection was carried out by observation techniques, in-depth interviews and documentation. The data were analyzed descriptively using a flow model developed by Miles and Huberman. The research results on the value of Islamic education in the malaqbiq Mandar culture are derived from several essential points. First, Kedzo or behaviour, namely behaviour in getting along in any environment, family, society, and work environment. It is in line with the Islamic view, which states that